Understanding pyramidal slip-induced deformation bands and dynamic recrystallization in AZWX3100 magnesium alloy - Risheng Pei; Fatim-Zahra Mouhib; Mattis Seehaus; Simon Arnoldi; Pei-Ling Sun; Talal Al-Samman (Journal of Magnesium and Alloys)
Dynamic recrystallization (DRX) in inhomogeneous deformation zones, such as grain boundaries, shear bands, and deformation bands, is critical for texture modification in magnesium alloys during deformation at elevated temperatures. This study investigates the DRX mechanisms in AZWX3100 magnesium alloy under plane strain compression at 200 °C. Microstructural analysis revealed necklace-type DRX accompanied by evidence of local grain boundary bulging. Additionally, ribbons of recrystallized grains were observed within fine deformation bands, aligned with theoretical pyramidal I and II slip traces derived from the matrix. The distribution of local misorientation within the deformed microstructure demonstrated a clear association between deformation bands and localized strain. Dislocation analysis of lamellar specimens extracted from two pyramidal slip bands revealed <c + a> dislocations, indicating a connection between <c + a> slip activation and the formation of deformation bands. Crystal plasticity simulations suggest that the orientation of deformation bands is responsible for the unique recrystallization texture of the DRX grains within these bands. The texture characteristics imply a progressive, glide-induced DRX mechanism. A fundamental understanding of the role of deformation bands in texture modification can facilitate future alloy and process design.